The Master Plan for Urban Transport and Mobility of Sorocaba - SP: challenges for the implementation of guidelines aimed at sustainable transport modes - Affonso, Stella Bruna Ananias; Magagnin, Renata Cardoso (National Journal of City Management, 2022)
The last decades have been marked by profound economic and social changes, which have significantly altered the population’s way of life. Among the main effects of urban agglomerations are changes in the transportation and mobility system that still represent a challenge for municipal management, especially in medium and large cities. As of Federal Law No. 12,587, dated January 3, 2012, all Brazilian municipalities with a population of over 20,000 inhabitants were required to prepare an urban mobility plan. In Sorocaba, the proposals directed to the requirements of this legislation are in the Urban Transportation and Mobility Master Plan (acronym in Portuguese, PDTUM), prepared between 2012 and 2013 and implemented in 2016. Aiming to analyze urban mobility in Sorocaba, this article brings a descriptive and partial evaluation of the guidelines contained in the PDTUM document related to non-motorized transport and public transport and its implementation in the municipality. For this analysis, some indicators of the Sustainable Urban Mobility Index (IMUS), developed by Costa (2008) are used, consisting of an important tool for mobility management and public policy formulation from the perspective of sustainability. Regarding the actions planned and already adopted in the municipality, some show efficiency and a need for expansion so that the improvements can be increasingly comprehensive. The results contribute to tracing a more precise scenario for mobility in Sorocaba and can be useful for other cities whose plans are under development or revision.